2012
DOI: 10.1242/jcs.094896
|View full text |Cite
|
Sign up to set email alerts
|

The 14-3-3 genepar-5is required for germline development and DNA damage response inCaenorhabditis elegans.

Abstract: Summary 14-3-3 proteins have been extensively studied in organisms ranging from yeast to mammals and are associated with multiple roles, including fundamental processes such as the cell cycle, apoptosis and the stress response, to diseases such as cancer. In Caenorhabditis elegans, there are two 14-3-3 genes, ftt-2 and par-5. ftt-2 is expressed only in somatic lineages, whereas par-5 expression is detected in both soma and germline. During early embryonic development, par-5 is necessary to establish cell polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Thus, these observations suggest that distinct mechanisms regulate the cortical inhibition of LET-99 at the anterior versus the posterior poles. Because 14-3-3 protein typically bind phosphorylated targets (reviewed in (Aristizabal-Corrales et al, 2012; Gardino and Yaffe, 2011; Obsil and Obsilova, 2011), the results reported here and in previous studies (Wu and Rose, 2007) support a model in which LET-99 is phosphorylated on 14-3-3 sites in the posterior by PAR-1 or a kinase downstream of PAR-1. Phosphorylated LET-99 then associates with PAR-5, which prevents LET-99's accumulation at the posterior-most cortex.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Thus, these observations suggest that distinct mechanisms regulate the cortical inhibition of LET-99 at the anterior versus the posterior poles. Because 14-3-3 protein typically bind phosphorylated targets (reviewed in (Aristizabal-Corrales et al, 2012; Gardino and Yaffe, 2011; Obsil and Obsilova, 2011), the results reported here and in previous studies (Wu and Rose, 2007) support a model in which LET-99 is phosphorylated on 14-3-3 sites in the posterior by PAR-1 or a kinase downstream of PAR-1. Phosphorylated LET-99 then associates with PAR-5, which prevents LET-99's accumulation at the posterior-most cortex.…”
Section: Discussionsupporting
confidence: 82%
“…Strong reduction in PAR-5 levels results in germ-line defects and sterility (Aristizabal-Corrales et al, 2012; Wang and Shakes, 1997). However defects in one-cell polarity can be observed in embryos derived from mothers with a partial loss of PAR-5 function generated by RNA interference (RNAi) or the use of maternal specific alleles (Morton et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SAGE analysis has indicated that these genes are expressed in dissected gonads, though multiple somatic gonad cells including the DTC are present in this sample (Xin Wang et al, 2009). Notably, pab-1 , W07E6.2, and par-5 have reported roles in germ cell proliferation (Aristizábal-Corrales et al, 2012; Ko et al, 2010; Voutev et al, 2006). Germline-expression profiling previously showed that his-72 , ran-1 , W07E6.2, and snr-2 are enriched in wild-type animals compared to germline-depleted mutants (Reinke et al, 2004), suggesting that these genes are expressed in the germline.…”
Section: Resultsmentioning
confidence: 99%